Meningkatkan Kemampuan Analisis Sintesis Siswa Dengan Metode Problem Solving Melalui Pengajaran Langsung - Muhammad Rizhan; M. Arifuddin Jamal; Sri Hartini (Universitas Lambung Mangkurat, 2013)
The low of synthesis analysis capabilities of students in resolving a problem or physical symptoms due to the lack of application of the method of problem-solving, so it caused low student learning outcomes. Therefore, conducted research that aims at improving the synthesis of analysis capabilities of students. Special purpose research to describe: (1) lesson plan implementation (2) procedural skill (3) learning outcomes (4) students response. The kind of research using classroom action research with Hopkins model that consisting of three cycles, each cycle includes plan, action/observation, and reflective. Data obtained through a test, observation, questionnaires, and documentation. The data were analyzed by descriptive qualitative and quantitative. Research findings: (1) lesson plan implementation in good categories (2) procedural skills students indicated synthesis analysis capabilities of students was increased (3) the students learning outcomes, that at present the percentage of classical exhaustiveness in cycles I 11,43% (not exhaustive), in cycles II 88,57% (exhaustive), in cycles III 94,29% (exhaustive) (4) the response of students to the problem solving methods through direct instruction in good categories.